Resolution of land disputes through mediation at the Sleman District land office - Ari Wibowo (Requisitoire Law Enforcement, 2023)
This research aims to describe the settlement of land disputes through mediation conducted by the Sleman District Land Office. What obstacles are encountered by the Sleman Regency Land Office in carrying out mediation of land disputes, as well as how the Sleman Regency Land Office tries to overcome these obstacles. This research is a descriptive research with a qualitative approach. The subjects of this research are the Sub-Section Head and staff of the Disputes and Conflicts Section of the Sleman Regency Land Office. Data collection used are interviews and documentation. The technique of checking the validity of data using cross-checking techniques, namely by checking the results of interviews with documentation data. The data was analysed inductively with steps including data reduction, data unitisation, data display and data conclusion and verification. The results showed that the settlement of land disputes through mediation at the Sleman District Land Office includes the stages of (1) complaints of land problems, (2) analysis of complaints of land problems, and (3) the mediation process for resolving land disputes. In resolving land disputes through mediation, the Sleman District Land Office faces various obstacles, namely: (1) the absence of the disputing parties, (2) the absence of good faith from each of the disputing parties, (3) differences in ability and education between the parties, (4) rules that are considered to slow down the dispute resolution process, because the Land Office as a mediator cannot be a decision maker. For these obstacles, the Sleman Regency Land Office overcame them by: (1) seeking mediation more than once a meeting, (2) emphasising good faith to the disputing parties in conducting mediation, (3) inviting the parties to be accompanied by trusted people to help convey arguments and evidence, (4) as well as in the internal Land Office is to appoint mediators who are ready in knowledge and ability.